Dynamic recrystallization and microstructural evolution in 40CrNi2MoV steel during forging - Wei Zhu; Xiaohe Wang; Luoxing Li; Peng Cheng; Chenxi Shao; Decheng Wang; Feng Feng; Peng Zhou (iScience)
Summary: Reactor pressure vessel (RPV) studs require uniform microstructures for reliability. A strain-compensated Arrhenius constitutive model and dynamic recrystallization (DRX) model for 40CrNi2MoV steel were established via isothermal compression (900°C–1180°C, 0.001–0.5 s−1). Finite element analysis predicted microstructural evolution of samples, validated by processing maps, and electron backscatter diffraction. At 900°C/0.5 s−1, discontinuous DRX dominated via grain boundary bulging, forming necklace-like structures, while higher temperatures or lower strain rates enhanced continuous DRX. Combined discontinuous and continuous DRX at 1060°C/0.05 s−1 yielded 99.28% DRX volume fraction and refined grains (25.2 μm). Simulations under optimized parameters (1180°C initial temperature, 15 mm/s die speed) revealed secondary DRX uniformly refining grains of RPV stud, reducing average size from 144 μm to 17 μm. This framework enables predictive control of microstructures for RPV studs.